Effectiveness of Debulking Liposuction in Secondary Inferior Extremity Fat–Predominant Lymphedema: Evaluation of the of Leg Dermal Backflow Improvement Using Indocyanine Green Lymphography - Antonia Valentine Puspasari; Parintosa Atmodiwirjo; Yefta Moenadjat; Mohamad Rachadian Ramadan (Jurnal Plastik Rekonstruksi, 2025)
Background:Secondary lymphedema with a predominant composition of fat is not effectively managed with physiological techniques. Instead, it necessitates debulking liposuction that reduces extremity circumference and improves lymph flow. This study aims to discover the effectiveness of improving lymphatic flow through indocyanine green lymphography examination.Methods: This retrospective cohort study involving secondary fat–predominant lower extremity lymphedema patients who underwent debulking liposuction in the Division of Reconstructive Plastic and Aesthetic Surgery, Department of Surgery, CMGH, in December 2022 - August 2024. The variables studied were the subject's lower extremity circumference and degree of leg dermal backflow before and after debulking liposuction.Results: Among 15 subjects, pre- and postoperative debulking liposuction measurements of inferior extremity circumference demonstrated significant reduction at 10 cm and 25 cm above the ankle, the patella, 10 cm and 25 cm above the knee. Postoperatively, 5 subjects with leg dermal backflow stage IV turned to stage II (1), III (4), while 10 subjects with the leg dermal backflow stage V turned to stage IV (9).Discussion: Reduction in the circumference of the inferior extremities after debulking liposuction at almost all measurement points except for the foot and ankle circumference. This related to the anatomy of lymphatic flow. Debulking liposuction showing a significant improvement in lymphatic flow, it clinically proven by the reduction dermal leg backflow degree after procedure.Conclusion: Debulking liposuction in secondary lower extremity lymphedema with a predominant composition of fat effectively reduces extremity circumference and improves lymphatic flow as evidenced by indocyanine green lymphographic examination.